Method Of Preventing Suture Failure In Sutures Of Performative Ulcers - PhD Ernazarov Khojimurod Irsaliyevich (Zien Journals, 2025)
To improve the reliability of tightness of sutures when suturing perforated gastric and duodenal ulcers in conditions of widespread peritonitis by improving the method of preventing suture failure
Keywords: perforated ulcer; suturing of perforation; nitric oxide